Impact of pilot and stoker torso angles in tandem para-cycling aerodynamics - Mannion, P.; Toparlar, Y.; Blocken, B.; Hajdukiewicz, M.; Andrianne, T.; Clifford, E. (Sports Engineering, 2019)
The torso angle of a cyclist is a key element to consider when attaining aerodynamic postures. For athletes competing in the tandem para-cycling category as the pilot or stoker, the torso angles are similar to those adopted by able-bodied athletes. However, their aerodynamic interaction is not yet fully understood. To date, there has been no study to identify aerodynamically advantageous torso angles for tandem athletes. In this study, numerical simulations with computational fluid dynamics and reduced-scale wind tunnel experiments were used to study the aerodynamics of tandem cyclists considering 23 different torso angle combinations. The sagittal torso angle combination of the pilot and stoker that yielded the lowest overall drag area of 0.308 m2 (combined pilot, stoker and bicycle) was 25° for the pilot coupled with 20° for the stoker. The results suggest that higher torso angles for the pilot have a lower impact on the overall drag area than equivalent torso angles for the stoker. This study suggests that a slight relaxation of pilot torso angle (which may help increase power output) may not penalise aerodynamics, in low (< 25°) sagittal torso angle ranges.